Kurikulum Merdeka: Strategi, Tantangan, dan Solusi Guru Pendidikan Agama Islam di SDIT Sunan Averroes Berbah Yogyakarta: Penelitian - Nisfu Kurniyatillah; Muh. Wasith Achadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research is motivated by the readiness and innovation of Islamic Education teachers at SDIT Sunan Averroes Berbah Yogyakarta in implementing the Merdeka Curriculum, particularly in the learning process that aligns with the principles and approaches of the curriculum. The purpose of this study is to describe the implementation of the Merdeka Curriculum, the learning strategies, as well as the challenges and solutions faced by Islamic Education teachers at SDIT Sunan Averroes Berbah Yogyakarta. The method used in this research is field research, with data collection techniques through direct observation in the field and interviews with relevant parties. The results show that the implementation of the Merdeka Curriculum by the Islamic Education teachers at the school has been running well, especially in classroom learning that emphasizes a contextual and student-centered approach. Therefore, the performance of Merdeka Curriculum implementation among Islamic Education teachers needs to be continuously encouraged and intensively guided by the principal so that the curriculum objectives and student learning outcomes can be achieved as expected.